DnDoggos. 1, Get the party started - Underhill, Scout (Feiwel and Friends, 2024)
"Four adorable dogs are tail-waggingly excited to play their favorite role-playing game in DnDoggos: Get the Party Started, the middle grade graphic novel debut from online comic creator Scout Underhill. They've picked their characters and favorite dice, and are ready to set off on the adventure their game master Magnus has created for them. Pickles, a rough and tumble fighter; Tonka, a playful and fun-loving bard; and Zoey, a wise and caring cleric, are given a quest to fetch a magical dog collar from a nearby swamp. But when they triumphantly return, they soon find that the collar isn't the only thing that has gone missing from Tail's Bend. All the squeaky toys in town have disappeared and Squish, the mayor's young son, has set off on his own to find them. It's up to the Doggos to rescue Squish, track down the missing toys, and save the day!"--Amazon.com.